Formation of Patriotism Of Bachelors In A Multicultural Environment Of Kazan Federal University - Maratovna Garifullina, Almira (2017)
The relevance of the research is due to the fact that the formation of patriotism of bachelors in a multicultural environment is an important aspect in the laying of professionally meaningful competences, tolerance, love for the Motherland and respect for world powers. Therefore, this article aims to study the level of patriotism of bachelors in a multicultural environment of the University. The article reveals the importance of patriotic education in the conditions of university education. The formation of patriotism is an integral part of modern life. As a result patriotism forms a positive perception of the surrounding reality while critical thinking develops which plays an important role in the formation of the student as an independently developing personality. Work on the formation of patriotism of bachelors in the multicultural environment of the university contributes to enriching knowledge about their homeland and the world as a whole. With such work, the civil position, responsibility and activity of the student are fixed taking into account the needs of the society. As a result of the experimental study, the initial levels of patriotism formation of bachelors in the university environment are given.